2015
DOI: 10.1111/ssqu.12150
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education and the Link Between Birth Timing and Children's School Readiness*

Abstract: Objective This study explored whether mothers’ education magnified the benefits of their fertility delays for their children. Methods Multiple-group path modeling assessed whether and why the positive association between mothers’ age at first birth and children’s test scores was greater for children of college educated women than children of other women. Results Older age at first birth was associated with higher math and reading test scores among the children of college educated women via their mothers’ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Their timing has implications for mothers’ and children’s achievement, health, and well-being (Royer, 2004; Loughran and Zissimopoulos, 2009; Augustine, Pricket, Kendig, and Crosnoe, 2015; Williams, Sassler, Addo, & Frech, 2015), and their timing affects population growth and decline. This study provides evidence that religious exposure during childhood and adolescence is related to the timing of subsequent births--nonmarital and marital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their timing has implications for mothers’ and children’s achievement, health, and well-being (Royer, 2004; Loughran and Zissimopoulos, 2009; Augustine, Pricket, Kendig, and Crosnoe, 2015; Williams, Sassler, Addo, & Frech, 2015), and their timing affects population growth and decline. This study provides evidence that religious exposure during childhood and adolescence is related to the timing of subsequent births--nonmarital and marital.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of first birth has been relatively neglected, although it carries significant consequences for women’s socioeconomic attainment and long-term health and well-being, along with the health and well-being of their children (Royer, 2004; Loughran and Zissimopoulos, 2009; Augustine, Pricket, Kendig, and Crosnoe, 2015; Williams, Sassler, Addo, & Frech, 2015). As women who have earlier first births are likely to have more births overall (Rindfuss, Morgan, and Swicegood, 1988; Mills, Rindfuss, McDonald and te Velde, 2011), studying the relationships between religion and the timing of first birth may additionally help us anticipate how macro-level religious change might affect population growth or decline.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, maturity or experience could be the key ingredient in shaping high human capital mothers’ decisions about other types of investments in children. Augustine et al (2015) showed that older age at first birth was associated with higher math and reading test scores among the children of college-educated women but not their less-educated counterparts; this is because college-educated mothers, but not other mothers, increased in both income and cognitive support for children with age.…”
Section: Introductionmentioning
confidence: 98%
“…Delaying a first birth beyond the teen years enables mothers to complete more schooling, begin a career, and acquire a host of other experiences that might contribute to a healthier prenatal environment as well as a wealthier, safer, and more stimulating postnatal environment for their first children (Haveman et al 1997; Hotz et al 2005; Augustine et al 2015; Miller 2011). These same advantages plus those associated with “on-the-job training” lessons from experiences rearing firstborn children may accrue to delays in second and subsequent births.…”
Section: Introductionmentioning
confidence: 99%